2011
DOI: 10.1159/000333268
|View full text |Cite
|
Sign up to set email alerts
|

Role of Radiofrequency Ablation in the Treatment of Hepatocellular Carcinoma: Experience of a Cancer Center in China

Abstract: Radiofrequency ablation (RFA) has become an important treatment for hepatocellular carcinoma (HCC). The good candidates for RFA are patients with HCC at an early stage (solitary tumor ≤5 cm in diameter or ≤3 nodules ≤3 cm in diameter). Several clinical trials have shown that RFA is effective in resection for the treatment of small HCC. Until now, RFA has been widely used as a radical treatment for small HCC. RFA also plays an important role in the multidisciplinary treatment of HCC and is usually combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The long-term survival rates are very low for TACE (5-year OS:1–8 %) [14]. Local treatments for unresectable HCC commonly used in combination with TAE/TACE for unresectable HCC are thermal ablation, percutaneous ethanol injection, and radiation therapy in Asian countries [13, 15]. Numerous clinical studies have reported improved outcomes using TACE + RT combination therapy compared with TACE [1618] or RT alone [19].…”
Section: Discussionmentioning
confidence: 99%
“…The long-term survival rates are very low for TACE (5-year OS:1–8 %) [14]. Local treatments for unresectable HCC commonly used in combination with TAE/TACE for unresectable HCC are thermal ablation, percutaneous ethanol injection, and radiation therapy in Asian countries [13, 15]. Numerous clinical studies have reported improved outcomes using TACE + RT combination therapy compared with TACE [1618] or RT alone [19].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past years, the rapid development and refinement of RF ablation technology has led to increasing use of this treatment modality in HCC patients [24] . Extensive clinical studies support RF ablation as a preferred treatment for very early HCC [25] . However, tumor recurrence, including LTP and IDR, frequently occurs, affecting the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Among the local ablative therapies, radiofrequency ablation (RFA) is the most widely used . It has the advantage of minimal invasiveness, making it the first‐line treatment for small HCC in patients with compromised liver function or associated severe medical conditions …”
Section: Introductionmentioning
confidence: 99%
“…10,11 It has the advantage of minimal invasiveness, 8,9 making it the first-line treatment for small HCC in patients with compromised liver function or associated severe medical conditions. 12,13 Elderly patients are more likely to have poor general conditions and associated medical diseases. 14 RFA has the advantage of being less invasive and it causes less pain, less blood loss, and earlier recovery than HR.…”
Section: Introductionmentioning
confidence: 99%